Sero-prevalence of Transfusion Transmissible Infections among Voluntary Blood Donors of Khulna Medical College Hospital - Alom, SM Tushar; Mondal, Kanak Jyoti; Tarafder, Shirin; Sonia, Farah Anjum; Chowdhury, Poritosh Kumar; Islam, Md Shoriful (Bangladesh Medical Journal, 2019)
Transfusion transmitted infections (TTI) are a great concern of safety for patients. Blood transfusion is a lifesaving procedure but always caries a potential risk of infections.The present study was designed to evaluate the prevalence of infectious disease markers and frequency in males and females of various age groups among healthy blood donors. A retrospective review of donor record over a period of 2 years between 2015 to2016 was done at the department of transfusion medicine Khulna medical college Hospital, Khulna, Bangladesh.Among the total 37,266 donors,358(0.96%) donors were infected and therefore not suitable for blood donations.HBV was found to be the most frequent infection with a total frequency of 0.72% followed by TP (0.20%), HCV (0.03%) and HIV (0.01%). None of the blood samples showed positivity for malarial parasite.Majority of the seropositive donors, (47.96%) were in the age group of 26 to 35 years followed by 29.47% in 18 to 25 years’ age group. Bangladesh Med J. 2017 May; 46 (2): 16-21